(untitled) (Global Journal of Human-Social Science, 2024)
The results of this study conducted between July and November 2019 have identified that a Clarias gabonensis value chain in the North part of Congo is principally dominated by men with regards to fishing activities and women with regard to the marketing of fish products harvested from the Lac T l Community Reserve LTCR to the cities of Impfondo Pokola and Oyo Both the fishing and the marketing are practiced by all age groups in the reserve and others localities Among fishermen 20 40 are over 55 years old and 69 60 are between 18 and 54 years old 34 69 have no education 38 77 have a primary level of education and 26 53 have a secondary level of education In comparison wholesalers and retailers have mainly a basic educational level 30 of the workforce is over 50 and over 70 have more than 10 years of experience in the business The absence of institutional investment in this value chain is demonstrated by the importance of internal investment resulting in dependence between the actors